Characterization of Mobile Augmented Reality Tasks Supported by Edge Computing Resources - Rodrigues, Karlla Chaves; Cardoso, Kleber Vieira; Correa, Sand Luz (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
Mobile Augmented Reality (MAR) applications rely on computationally intensive and latency-sensitive tasks such as Simultaneous Localization and Mapping (SLAM) and object detection, which challenge mobile devices. Offloading these workloads to edge servers is promising, yet realistic workload and traffic models remain scarce, especially under heterogeneous CPU–GPU infrastructures. This paper presents an empirical characterization of computational demand, memory usage, and IP traffic generated by SLAM and YOLObased object detection using an enhanced MR-Leo prototype (eMR-Leo). Experiments are conducted under controlled conditions with USB tethering to isolate application-level traffic. Results show that SLAM is CPU-bound with limited gains from GPU acceleration, while object detection is highly parallel and benefits significantly from GPU offloading. Object detection latency is reduced from 148 ms to approximately 4 ms per frame (approximately 98% reduction), enabling real-time performance. Based on these measurements, we derive statistical workload models for both tasks, covering instruction counts, memory usage, and traffic patterns, supporting realistic simulation and performance evaluation of edge-assisted MAR systems.